2014
DOI: 10.1021/ja505899g
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Intermediates Along the Transition from Polyproline I to Polyproline II Using Ion Mobility Spectrometry-Mass Spectrometry

Abstract: Polyproline exists predominately as the all-cis polyproline I (PPI) helix in aliphatic alcohols, whereas the all-trans polyproline II (PPII) helix is favored in aqueous solutions. Previous ion mobility spectrometry-mass spectrometry (IMS-MS) work demonstrates that the gas-phase conformations of polyproline ions can be related to the corresponding PPI and PPII helices in solution [J. Phys. Chem. B 2004, 108, 4885]. Here, we use IMS-MS to examine the detailed intermediate steps associated with the process of Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(166 citation statements)
references
References 82 publications
5
160
0
1
Order By: Relevance
“…It is clear that the majority of the population cannot originate in the gas phase and, thus, there remain only two alternatives: it either reflects the population of this conformer in solution, which survives the electrospray process, or the conditions in the electrospray droplets. A possible way to address this question would be to change the solution conditions, for example by changing the solvent or concentration of the solute and measuring the cis-Pro to trans-Pro ratio in the ion mobility spectra [19,66].…”
Section: The Case For Quasi-equilibrium and Kinetic Trapping From Solmentioning
confidence: 99%
“…It is clear that the majority of the population cannot originate in the gas phase and, thus, there remain only two alternatives: it either reflects the population of this conformer in solution, which survives the electrospray process, or the conditions in the electrospray droplets. A possible way to address this question would be to change the solution conditions, for example by changing the solvent or concentration of the solute and measuring the cis-Pro to trans-Pro ratio in the ion mobility spectra [19,66].…”
Section: The Case For Quasi-equilibrium and Kinetic Trapping From Solmentioning
confidence: 99%
“…[13] Proline is unique amongst naturally occurring amino acids as the only residue able to readily form both cis and trans configurations about its peptide bond linkages, [14] thereby permitting two different helical structures to exist for poly-l-proline. [15] Theall-cis right-handed helix (Form I, PP-I) is tightly wound, [16] while the all-trans left-handed helix (Form II, PP-II) adopts al ess dense geometry (Figure 1). [17] Theavailability of these similar, yet fundamentally different, poly-l-proline helices makes them excellent choices for exploring the connection between molecular structure,l owfrequency vibrational motions,and bulk elastic constants.…”
Section: In Memory Of Roberto Orlandomentioning
confidence: 99%
“…These results are consistent with previous studies of the poly-l-proline transformation, which found that large activation energy barriers exist along the conversion coordinate. [15,29] Themeasurement of biopolymer elasticity through acombined approach of THz-TDS experiments and ss-DFT simulations enables quantification of molecular rigidities to be achieved in arelatively straightforward way.This methodology has yielded the previously unmeasured Youngs moduli of the widespread poly-l-proline polypeptide in both its helical forms,a nd revealed them to be considerably more elastic than expected. This prompts contemplation of their role as an analytical standard for rigidity.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Proline is unique amongst naturally occurring amino acids as the only residue able to readily form both cis and trans configurations about its peptide bond linkages,14 thereby permitting two different helical structures to exist for poly‐ l ‐proline 15. The all‐ cis right‐handed helix (Form I, PP‐I) is tightly wound,16 while the all‐ trans left‐handed helix (Form II, PP‐II) adopts a less dense geometry (Figure 1).…”
mentioning
confidence: 99%